Hidden diversity in Daptomys (Rodentia: Cricetidae): a new species from lower montane forests of central Peru - Pacheco, Víctor; Sánchez-Vendizú, Pamela; Fajardo, Úrsula; Cossíos, Daniel; Cadenillas, Richard (Zootaxa, 2025)
Daptomys Anthony, 1929, comprises at least five species, distributed in lower and premontane Neotropical forests from Venezuela to Bolivia, but its real diversity is likely underestimated. During recent expeditions to Tingo María National Park, Huánuco Department, in central Peru, we collected two specimens of Daptomys in premontane forest, that represent a new lineage. Here, we present an integrative approach combining coalescent phylogenetic analyses (based on cytochrome b and three nuclear gene sequences), along with morphological and morphometric data, to support the recognition of the Huánuco specimens as a new species of Daptomys, which we describe in this paper. The new species can be distinguished from other congeners by a unicolored tail ending in a distinct pencil of white hairs, a very small toothrow, anteriorly expanded nasals, a very short incisive foramina, a long palate with a prominent median process, and a large postglenoid foramen. In addition, the species delimitation methods recovered D. musseri as a valid species which is supported also by morphological and morphometric differentiation and distribution pattern.